La mémoire partagée de « la vie de café » dans les quartiers populaires centraux d’immigration - Catherine Gauthier (Ambiances)
Studying immigrants’ memories in the popular districts of downtown old Saint-Etienne, Catherine Gauthier, sociologist, and Sandrine Binoux, photographer, capture atmospheres and portraits in the cosmopolitan cafés of five districts. This has resulted in a 35-minute film, retracing memories and present atmospheres of these establishments. The article shows how the street, the factory, and migratory life have shaped them, and then how their activity flows over into the public space very spontaneously. Initially an urban resource for newcomers, today the cafés can become an emblem of local memory. The research and the film allow us to visit the history of the declining commercial central locations, and to chart the traces of a vernacular culture of socio-cultural diversity.